OPTIMALISASI KEUANGAN UMKM MENGGUNAKAN TEKNOLOGI MASA KINI DENGAN APLIKASI SIAPIK - Istianingrum, Rika; Nurlia; Yusuf, Tamsil; Maharani, Dewi; Nuraini, Kintan Ika (Batara Wisnu : Indonesian Journal of Community Services, 2025)
MSMEs have an important role in local economic growth, but still face challenges in systematic financial management. One solution offered is the utilization of the SIAPIK application (Sistem Informasi Aplikasi Pencatatan Informasi Keuangan), a free application developed by Bank Indonesia to help record financial transactions digitally. This activity aims to socialize the use of SIAPIK to MSME players in Rintik Village, Babulu District, Penajam Paser Utara Regency, East Kalimantan. The methods used in this activity include socialization, hands-on training, and assistance for businesses in implementing SIAPIK. The results of this activity showed that participants' understanding of the importance of financial records increased, and there was an increase in the use of the SIAPIK application to help record business income and expenses. SIAPIK implementation is expected to improve digital financial literacy and help MSMEs in making more accurate data-based decisions.